If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(3x + -5) + 8x + -2 = 0 Reorder the terms: -2(-5 + 3x) + 8x + -2 = 0 (-5 * -2 + 3x * -2) + 8x + -2 = 0 (10 + -6x) + 8x + -2 = 0 Reorder the terms: 10 + -2 + -6x + 8x = 0 Combine like terms: 10 + -2 = 8 8 + -6x + 8x = 0 Combine like terms: -6x + 8x = 2x 8 + 2x = 0 Solving 8 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 2x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 2x = 0 + -8 2x = 0 + -8 Combine like terms: 0 + -8 = -8 2x = -8 Divide each side by '2'. x = -4 Simplifying x = -4
| -12x+7=5x-2x^2 | | 9x+12=8x | | 3x^2+12x+-1=0 | | -1=(1/6)x-2 | | -8=(1/6)x-2 | | 2x-(x+1)=-3+5(x-6) | | 7x^2+3x=12 | | 3y-3+y+45=5+7y+45-5y | | 10+6= | | 5x+6=5(x+9) | | (-2.5)6x-2=(-2.5)7x+4 | | (5x-4)+(2x+11)= | | 6+6(b+2)=23+6b | | -9c+5=-40 | | 7(2q-3)=6q+3 | | -5(t+4)= | | 6x+4(3x-8)=16 | | 3a=-3(-13-3a) | | 31-19=3(x-1) | | 31+3y-3=14y-14-5y | | -5-4a+3=6a-8 | | 4x+18=-8 | | 5=7h+14 | | 3(1+8x)-8x=7x-6 | | 6t+11=8t-15 | | (x-10)+(2x+40)= | | -8x-2=-20+6x+6x | | -7m-17=11 | | 18-4x=13+x | | 38+6x=4(1-7x) | | 69-5x=13x+21 | | 6+7a=-3+9a-9 |